PELESTARIAN ALEK SIMARAJO LELO DI NAGARI CUPAK - Suci Hadisti; Erniwati Erniwati (Ensiklopedia of Journal, 2023)
Abstract: This article discusses the Preservation of Alek Simarajo Lelo in the Cupak Community: From Traditional Ceremonies to Art Performances in 1984-2015. This research is historical research through the stages of heuristics, verification/criticism, interpretation, and historiography. Sources were obtained through informants in Nagari Cupak, Penghulu Empat Jinih, Wali's Office staff, witness Alek Simarajo Lelo from the local community. Meanwhile, secondary sources were obtained through literature studies to obtain sources in the form of books and journals, document studies in the form of photographs of Alek Simarajo Lelo, as well as field studies by means of interviews and observations. This article shows that the results of this study indicate that the Preservation of Alek Simarajo Lelo in the Cupak Community: From Traditional Ceremonies to Art Performances in 1984-2005 underwent a change in the implementation in the form of performing arts in the form of alek rows and costumes. 1) The clothes of the Kudo Baganto line up are at the front, which are worn by young children who are not wearing the traditional black clothes of the ninik mamak. 2) rows of patiak sanggua playing talempong and modern musical instruments pupuik. 3) rows of parents and bundo kanduang maanta nasi (parents) not wearing basiba-cut black brackets. On the other hand, there are factors that cause alek to no longer be carried out in the form of customary marriages, namely changes in mindset, economics and socio-cultural factors.Keywords: Preservation, Alek Simarajo Lelo, Art Show, Cupak VillageKeywords: Well Known Mark, Madrid Protocol, Development Legal Theory